Information Security Technology for Applications 16th Nordic Conference on Secure IT Systems, NordSec 2011, Tallinn, Estonia, October 26-28, 2011, Revised Selected Papers - Laud, Peeter; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 16th International Conference on Secure IT Systems, NordSec 2011, held in Tallinn, Estonia, October 26-28, 2011. The 16 revised papers presented together with 2 invited talks were carefully reviewed and selected from 51 submissions. The papers are organized in topical sections on applied cryptography, commercial security policies and their enforcement, communication and network security, security modeling and metrics, economics, law and social aspects of security, and software security and malware.
Keywords: Computer science; Computer security; Data structures (Computer science).; Data encryption (Computer science).; Coding theory; Management information systems; Computer Science; Systems and Data Security; Data Structures, Cryptology and Information Theory; Coding and Information Theory; Data Encryption; Information Systems Applications (incl. Internet).; Management of Computing and Information Systems; Electronic books